2020
DOI: 10.1111/jfpp.14712
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric nanoparticles loaded with Baccharis dracunculifolia DC essential oil: Preparation, characterization, and antibacterial activity in milk

Abstract: Eudragit RS100 nanoparticles containing Baccharis dracunculifolia DC essential oil (N‐EO) was developed by the nanoprecipitation method. N‐EO presented an average diameter of 151.6 nm, zeta potential (ζ) of +51.7 mV, and encapsulation efficiency of 99.4%. The antibacterial activity of N‐EO and free essential oil (EO) was evaluated in BHI broth against Staphylococcus aureus, Bacillus cereus, Listeria monocytogenes, and Salmonella Enteritidis. No viable cell counts were detected for all strains tested up to 4 hr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…The expected benefits from the encapsulation of plant-based products included an enhanced aqueous solubility and bioavailability, a better protection from the environment (pH, temperature, humidity and oxygen) and a persistent delivery (Bilia et al, 2014). Several studies have been dedicated to the encapsulation of plant derived-metabolites such as essential oil (EO) (Chifiriuc et al, 2017;El-Asbahani et al, 2015;Froiio et al, 2019;Herculano et al, 2015;Jummes et al, 2020;Partheniadis et al, 2020;Pina-Barrera et al, 2019;Timbe et al, 2020), vegetable oils (Contri et al, 2013(Contri et al, , 2016Lammari et al, 2020a;Sousa et al, 2013), plants extracts (Azeez et al, 2020;Mughees et al, 2020;Servat-Medina et al, 2015), etc. However, to the best of our knowledge, neither the extract nor the EO of costus roots have been previously encapsulated in polymeric nanoparticles.…”
Section: Polymentioning
confidence: 99%
“…The expected benefits from the encapsulation of plant-based products included an enhanced aqueous solubility and bioavailability, a better protection from the environment (pH, temperature, humidity and oxygen) and a persistent delivery (Bilia et al, 2014). Several studies have been dedicated to the encapsulation of plant derived-metabolites such as essential oil (EO) (Chifiriuc et al, 2017;El-Asbahani et al, 2015;Froiio et al, 2019;Herculano et al, 2015;Jummes et al, 2020;Partheniadis et al, 2020;Pina-Barrera et al, 2019;Timbe et al, 2020), vegetable oils (Contri et al, 2013(Contri et al, , 2016Lammari et al, 2020a;Sousa et al, 2013), plants extracts (Azeez et al, 2020;Mughees et al, 2020;Servat-Medina et al, 2015), etc. However, to the best of our knowledge, neither the extract nor the EO of costus roots have been previously encapsulated in polymeric nanoparticles.…”
Section: Polymentioning
confidence: 99%
“…In fact, no hemolysis was observed in the two drug-free EuNPs across the same concentration range (10–1000 μg/mL). This indicated that the excipients used in the FE eye drop formulations were not cytotoxic [ 66 , 67 ]. As the FE concentration increased, hemolytic activity increased in a dose-dependent manner.…”
Section: Resultsmentioning
confidence: 99%
“…Not showing activity against Gram-negative bacteria and yeasts ( Timbé et al, 2021 ). This same research group also evaluated the antimicrobial activity of nanoparticles containing B. dracunculifolia oil ( Harmonia Natural - Canelinha, SC, Brazil) ( Timbé et al, 2020 ). First, the MBC of the oil was analyzed against Listeria monocytogenes (0.56 mg/ml), S. aureus (0.28 mg/ml), B. cereus (0.14 mg/ml) and S. Enteritidis (1.13 mg/ml).…”
Section: Pharmacology and Bioactivitymentioning
confidence: 99%
“…After 4 h of contact of the essential oil with S. aureus , B. cereus, and L. monocytogenes, and S. Enteritidis, there were no more viable cells. The reduction achieved by the nano encapsulated oil was 2 h of incubation for B. cereus , 10 h for L. monocytogenes, and 24 h for S. aureus and S. Enteritidis, suggesting a gradual release of compounds with antimicrobial activity ( Timbé et al, 2020 ).…”
Section: Pharmacology and Bioactivitymentioning
confidence: 99%